Study of the rare decays of B0s and B0 mesons into muon pairs using data collected during 2015 and 2016 with the ATLAS detector - Aaboud, Morad; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Franchino, Silvia; Geisler, Manuel Patrice; Hanke, Paul; Jongmanns, Jan; Kugel, Andreas; et al. (Journal of high energy physics, 2019)
A study of the decays B s 0 → μ+μ− and B0 → μ+μ− has been performed using 26.3 fb−1 of 13 TeV LHC proton-proton collision data collected with the ATLAS detector in 2015 and 2016. Since the detector resolution in μ+μ− invariant mass is comparable to the B s 0 -B0 mass difference, a single fit determines the signal yields for both decay modes. This results in a measurement of the branching fraction B(B0s→μ+μ−)=(3.2+1.1−1.0)×10−9B(Bs0→μ+μ−)=(3.2−1.0+1.1)×10−9 \mathrm{\mathcal{B}}\left(B_s^0→ μ^{+}{μ}^{-}\right)=\left({3.2}_{-1.0}^{+1.1}\right)× {10}^{-9} and an upper limit B(B0→μ+μ−)<4.3×10−10B(B0→μ+μ−)<4.3×10−10 \mathrm{\mathcal{B}}\left(B^0→ μ^{+}{μ}^{-}\right)<4.3× {10}^{-10} at 95% confidence level. The result is combined with the Run 1 ATLAS result, yielding B(B0s→μ+μ−)=(2.8+0.8−0.7)×10−9B(Bs0→μ+μ−)=(2.8−0.7+0.8)×10−9 \mathrm{\mathcal{B}}\left(B_s^0→ μ^{+}{μ}^{-}\right)=\left({2.8}_{-0.7}^{+0.8}\right)× {10}^{-9} and B(B0→μ+μ−)<2.1×10−10B(B0→μ+μ−)<2.1×10−10 \mathrm{\mathcal{B}}\left(B^0→ μ^{+}{μ}^{-}\right)<2.1× {10}^{-10} at 95% confidence level. The combined result is consistent with the Standard Model prediction within 2.4 standard deviations in the B(B0→μ+μ−)−B(B0s→μ+μ−)B(B0→μ+μ−)−B(Bs0→μ+μ−) \mathrm{\mathcal{B}}\left(B^0→ μ^{+}{μ}^{-}\right)-\mathrm{\mathcal{B}}\left(B_s^0→ μ^{+}{μ}^{-}\right) plane. Open image in new window